ELIMINASI PROTEIN SECARA ELEKTROFORESIS PADA PEMBUATAN GULA KELAPA - . Giyarto (JURNAL AGROTEKNOLOGI, 2007)
Coconut palm sugar, sweetener, brown color and aroma agent, is produced by cooking of nira. On the other hand, the developing business of coconut palm sugar still has problem on the several of its quality, especially on the brown color appearance caused by high intensity of browning reaction and the usage of food additive agent. High intensity of browning reaction could be reduced by elimination of protein molecules in nira through electrophoresis technique. The objectives of this research are to identify the electrophoresis conditions i.e pH, voltage supply, and duration that eliminate the greater protein molecules; and to analyze the influences of this treatment on the coconut palm sugar qualities. Result of the research showed that electrophoresis treatment performed on the following conditions : pH 7, and voltage supply 100 volts for 5 hours, was eliminated the protein molecules of nira effectively, which could increased the total sugar and glucose, but decreased the Maillard reaction, Na-bisulphate consumption, and the color of coconut palm sugar. Keywords: nira, coconut palm sugar, electrophoresis